ASSESSMENT OF ENVIRONMENTAL POLLUTION OF WATER FROM IRRIGATION CANAL (ALEKSANDROVAČKI CANAL, SERBIA) USING PHYTO-INDICATORS - S. Gvozdenac; D. Inđić; S. Vuković; V. Bursić; J. Tričković (Journal of Animal and Plant Sciences, 2014)
The aim of this study was to carry out comparative assessment of pollution level of water from Aleksandrovački canal, Serbia, using both chemical methods and phytoindicators, and to estimate its potential use for irrigation of four most commonly cultivated plant species in this area (maize, barley, cucumber and white mustard). The effect of water quality and/or pollution was assessed in bioassay, according to changes in physiological (seed germination energy, germination) and morphological parameters (root and shoot length -cm and fresh and dry weight of root and shoot-g) of tested species. The chemical analysis of water determined a high content of suspended substances, nutrients, ammonium ion, total nitrogen, organic matter with low degradability, total organic carbon, orthophosphates, total phosphorus, arsenic and chromium. The response of phyto-indicators to water quality and mixed pollution was species-dependant. Germination of maize, cucumber and white mustard was not under the influence of water quality, while barley seeds germinated in significantly lower percentage in water from the canal (95%) compared to the control (100%). Canals water inhibited root elongation of maize and barley and stimulated of white mustard (p<0.01) compared to the control. Shoot length of barley, cucumber and white mustard was not under the influence of water quality (p>0.05). Biomass was differently affected by water from the canal.
Keywords: Canal water; pollution; irrigation; plants; bioindicators